2019
DOI: 10.31857/s0869-5903276658-689
|View full text |Cite
|
Sign up to set email alerts
|

Petrological-geochemical characteristics of lavas, sources and evolution of magmatic melts of the Kazbek neovolcanic center (Greater Caucasus)

Abstract: The results of petrological-geochemical and isotope-geochemical studies of the Late Pleistocene-Holocene lavas of the Kazbek Neovolcanic Center, one of the largest centers of youngest magmatism in the Greater Caucasus, are presented. It has been established that the volcanic rocks of the Kazbek center arise a continuous compositional series basaltic (trachy-)andesites(trachy-)andesitesdacites with a predominance of calc-alkaline intermediate and moderately-acid lavas. The obtained results indicate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…By contrast, to increase from least to the most radiogenic Gudauri Formation, lava would require excessive amounts of crustal assimilation, inconsistent with its bulk chemistry. It should be noted that Parfenov et al (2019) have suggested that Jurassic sediments from the Mt. Kazbek region could be a potential candidate for a crustal contaminate, but although they have elevated 87 Sr/ 86 Sr ratios (0.718621), their low Sr content (80 μg g −1 ) would again require large (Neill et al, 2015).…”
Section: Crustal Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, to increase from least to the most radiogenic Gudauri Formation, lava would require excessive amounts of crustal assimilation, inconsistent with its bulk chemistry. It should be noted that Parfenov et al (2019) have suggested that Jurassic sediments from the Mt. Kazbek region could be a potential candidate for a crustal contaminate, but although they have elevated 87 Sr/ 86 Sr ratios (0.718621), their low Sr content (80 μg g −1 ) would again require large (Neill et al, 2015).…”
Section: Crustal Contaminationmentioning
confidence: 99%
“…suggest there is a common Caucasus mantle composition that is represented by trachy-basalts similar to oceanic island basalts (OIB) erupted in central Georgia, such that intermediate composition rocks from the central range of the Greater Caucasus have undergone small amounts of crustal assimilation (e.g. Parfenov et al, 2019), whereas the silicic volcanics of the western range require significant (50%) crustal assimilation (e.g. Lebedev et al, 2010).…”
Section: Introductionmentioning
confidence: 99%